Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Turnover Intention Dengan Stress Kerja Sebagai Variabel Intervening - Santoso, Kiki Rahmawati; Adriansyah , Ahmad; Simatupang , Batara Maju; Joyosumarto , Subarjo; Haryanti , Enny (STIE Indonesia Banking School, 2024)
This study aims to analyze the influence of workload on job stress, the influence of the work environment on job stress, the influence of workload on turnover intention, the influence of the work environment on turnover intention, and the influence of job stress on turnover intention. This research uses a quantitative method with a survey approach. Researchers collected data by distributing questionnaires. The population in this study is all employees of the Smalrt Branch Bank Mandiri Banking in Region IV Jakarta 2, totaling about 100 respondents. The sampling technique in this study is saturation sampling, where all population members are used as samples, resulting in 100 respondents in this research. In this study, data processing and evaluation are done using Structural Equation Modeling (SEM PLS) with the software Smart PLS 3.0.The results of the study show that there is a significant positive influence of workload and the work environment on job stress. There is no significant influence of workload on turnover intention. There is a significant positive influence of the work environment and job stress on turnover intention. For future researchers, it is recommended to further develop this study with other variables such as competency, leadership, and compensation existing in Bank Mandiri.